2022
DOI: 10.1002/arch.21953
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation and parasitism affect the ability of larval hemocytes of Anastrepha obliqua for phagocytosis and the production of reactive oxygen species

Abstract: The development of the parasitoid Doryctobracon crawfordi (Viereck) (Hymenoptera: Braconidae) in Anastrepha obliqua (McQuart) (Diptera: Tephritidae) larvae is unviable in nature; however, if the host larva is irradiated at 160 Gy, the parasitoid develops and emerges successfully. This suggests that radiation affects the immune responses of A. obliqua larvae, while the underlying mechanisms remain to be revealed. Using optical and electronic microscopies we determined the number and type of hemocyte populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Regarding the immune response of A. obliqua to parasitoids, it has been reported that its larva possesses 5-6 types of haemocytes that generate a strong immune response (phagocytosis and production of reactive oxygen species) (Silva et al 2002;Gómez-Alonso et al 2022). The presence of these haemocytes resulted in the melanization and encapsulation of the first immature stages of parasitoids (Silva et al 2002;), which has not been observed in A. ludens (Poncio et al 2016; 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the immune response of A. obliqua to parasitoids, it has been reported that its larva possesses 5-6 types of haemocytes that generate a strong immune response (phagocytosis and production of reactive oxygen species) (Silva et al 2002;Gómez-Alonso et al 2022). The presence of these haemocytes resulted in the melanization and encapsulation of the first immature stages of parasitoids (Silva et al 2002;), which has not been observed in A. ludens (Poncio et al 2016; 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Anastrepha larvae, little information is available on their capacity of immunological reaction to parasitoids. An exception is A. obliqua (Silva et al, 2002; Gómez‐Alonso et al, 2022), which has the ability to suppress the development of immature stages of native parasitoids – Doryctobracon crawfordi (Viereck) or Opius hirtus (Fischer) –, also possibly the result of a coevolutionary relationship (Poncio et al, 2015; Gómez‐Alonso et al, 2022). However, the development of D. longicaudata in A. obliqua larvae is viable, although at a lower level of emergence, based on results reported both in the laboratory and in the field (Sivinski et al, 1997; Isiordia‐Aquino et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…When ionizing radiation is applied to lung tissue, it ionizes water molecules and generates a significant amount of ROS (27)(28)(29). These ROS can damage the DNA, proteins, and lipid membranes of target cells.…”
mentioning
confidence: 99%